The Influence of Trust and Perceived of Risk on Purchase Decisions in e-Commerce Shopee at Students of The Faculty Economics and Business, University State of Makassar - Nurul Fanaysillah Muchtar; Chalid Imran Musa; Muh. Ichwan Musa; Siti Hasbiah; Ilham Wardhana Haeruddin (PT. Maju Malaqbi Makkarana, 2023)
The purpose of this study was to determine the effect of trust and perceived risk on purchasing decisions at E-commerce Shopee partially and simultaneously. The sample used was 100 students of the Faculty of Economics and Business who had been selected based on predetermined criteria. Data collection techniques were carried out using questionnaires and literature study. Data analysis techniques consist of validity test, reliability test, classic assumption test consisting of normality test, multicollinearity test, and heteroscedasticity test, multiple linear analysis test, hypothesis test, test of the coefficient of determination. The Trust variable has a positive and significant influence on purchasing decisions, the Perceived Of Risk variable has a positive and significant influence on purchasing decisions. the dependent variable of purchasing decisions can be explained by variables consisting of Trust and Perceived Of Risk, the rest is explained by other variables that were not examined in this study